Способ контроля сопротивления изоляции обмоток электродвигателя в мехатронной системе - Гарганеев А. Г. Александр Георгиевич; Каракулов А. С. Александр Сергеевич; Машинский В. В. Вадим Викторович; Завертан С. Н. Сергей Николаевич; Коломенский О. И. Олег Игоревич
опубл. 27.06.13